Unique and Transdiagnostic Symptoms of Hypomania/Mania and Unipolar Depression. (May 2019) - Stanton, Kasey; Khoo, Shereen; Watson, David; Gruber, June; Zimmerman, Mark; Weinstock, Lauren M.
Extensive research has been conducted to isolate features that distinguish bipolar spectrum disorders from unipolar depression. Therefore, we identified latent symptom dimensions that are unique versus shared across these disorders by examining the joint structure of hypomanic/manic and depressive symptoms in two large samples (i.e., 647 community adults; 1, 370 outpatients with unipolar depression or bipolar disorder history). Results across studies suggested that (a) many hypomanic/manic and depressive symptoms (e.g., irritability) are transdiagnostic, but also that (b) symptoms such as increased energy and euphoric mood define a latent specific positive activation dimension that appears more specific to bipolar disorder. We discuss how these results indicate that some symptoms may be more optimal to target than others when trying to distinguish bipolar disorder from unipolar depression, as well as how the identification of relatively disorder-specific symptom types may optimally guide future research on key mechanisms linked to hypomania/mania and depression.